A research framework for user centered web development - Ayu, Media Anugerah; Zakaria, Noor Azura (IIUM Press, 2011)
Web is a prominent tool in the organization III order to sustain the competitiveness globally. With the facilities available in the market and internet wise, the web development is becoming much easier to be done. However, in the organization context, the web cannot be simply developed without concerning on the user's requirements. The quality must be made and the satisfaction from the end users towards the website must be sustained. The usability of the website is vital in order to attract more customers to visit the website. It is also one of a ways to uphold competitive advantage. Therefore, the user-centred technique is considered as an appropriate technique for the organization to produce usable website